Antibacterial Nanocomposite of Poly(Lactic Acid) and ZnO Nanoparticles Stabilized with Poly(Vinyl Alcohol): Thermal and Morphological Characterization. Issue 1 (2nd January 2019) - Restrepo, I.; Flores, P.; Rodríguez-Llamazares, S.
ABSTRACT: The effect of polyvinyl alcohol (PVA) as a surface coating agent on the antibacterial and thermal properties of polylactic acid (PLA)/ZnO nanocomposites prepared by melt blending was investigated. The ZnO nanoparticles were coated and stabilized with PVA using a solvothermal method. Nanocomposites were prepared with different ZnO nanoparticle content: 1, 3 and 5 wt.%. Electron transmission microscopy and Fourier transform infrared spectroscopy showed the presence of a layer around the nanoparticles and the interaction between nanoparticles and PVA, respectively. DSC analysis revealed that the thermal properties of the nanocomposites were not affected by the coating of ZnO nanoparticles with PVA. The PLA/ZnO nanocomposites with coated nanoparticles presented better antibacterial activity than those containing uncoated nanoparticles. Graphical Abstract: